Cold Shock Domain Containing E1 (CSDE1) Protein is Overexpressed and Can be Targeted to Inhibit Invasiveness in Pancreatic Cancer Cells. Issue 10 (24th April 2020) - Liu, Hui; Li, Xiang; Dun, Matthew D.; Faulkner, Sam; Jiang, Chen Chen; Hondermarck, Hubert
Abstract: Pancreatic cancer has a dismal prognosis and to date there are no targeted therapies for this malignancy. Using shotgun proteomics, the mRNA binding protein cold shock domain containing E1 (CSDE1), also called upstream‐of‐N‐Ras, is detected in pancreatic cancer cell lines but not in normal pancreatic epithelial cells. The expression of CSDE1 in pancreatic cancer cells is confirmed by Western blotting and immunohistochemistry of human pancreatic tumors. In vitro functional assays show that siRNA downregulation of CSDE1 or gene knockout using CRISPR‐Cas9 significantly reduce the invasiveness of pancreatic cancer cells. Together, this study reveals that CSDE1 is overexpressed in pancreatic cancer and is a potential therapeutic target to inhibit pancreatic cancer cell invasion.